Model‐based design of project systems, modes, and states. Issue 2 (10th July 2019) - Shafaat, Ali; Kenley, C. Robert
Abstract: The field of project management has been trying to find generalizable sets of rules, and this article applies approaches and methods from systems engineering to develop such rules that support flexible project design. It presents an approach for modeling projects that divides project systems into three interacting subsystems (planned, executed, and interface systems) and proposes a framework for designing projects that integrates project implementation, verification, and validation. To build a generalizable model, this article revisits the notation of modal systems developed by Wymore and combines it with more recent developments in systems engineering, project design, and management. The temporary and changing environments of projects are addressed by adjusting the Wymorian definitions and related mathematical models to represent projects as a sequence of transient modes rather than activities. This approach enables better design and control of projects by reducing uncertainty and its consequences through a systematic framework for planning, monitoring, and controlling projects.